Challenges Of Indonesian Small Micro Enterprises (MSEs) In Fulfilling Halal Certification Obligations October 2024 - Naisabur, Nanang; Putra, Haris Maiza (Ta'amul: Journal of Islamic Economics, 2024)
The challenge of mandatory halal regulations contained in Law Number 33 of 2014 concerning Halal Product Guarantees (UU JPH) and its derivatives, means that products entering, circulating and being traded in Indonesian territory must be halal certified. However, until now there are still micro and small enterprises (MSEs) in Indonesia that have not fulfilled this requirement. So the Indonesian government, in this case BPJPH, needs Pentahelix synergy by providing stricter outreach to business actors in its implementation. The aim of this research is to reveal the challenges faced by micro and small enterprises (UMK) throughout Indonesia in fulfilling halal certification obligations. The method used in this research is analytical descriptive analysis, namely describing and analyzing the challenges of micro and small enterprises (UMK) throughout Indonesia in fulfilling halal certification obligations. The research results prove that based on the JPH regulations, there are 3 product groups that must be halal certified as of October 17 2024, namely first, food and beverage products. Second, raw materials, food additives and auxiliary materials for food and beverage products. Third, slaughtered products and slaughtering services. For micro and small enterprises (UMK) throughout Indonesia who have not carried out their halal certification obligations, they will be subject to sanctions in the form of written warnings, administrative fines, and the withdrawal of goods from circulation. It was stated that the sanctions applied were in accordance with the provisions in PP No. 39/2021 concerning the Implementation of the Halal Product Guarantee Sector. Keywords: Micro and Small Enterprises, Halal Certification, Mandatory Halal